Linking serpentinization, hyperalkaline mineral waters and abiotic methane production in continental peridotites: an integrated hydrogeological-bio-geochemical model from the Cabeço de Vide CH4-rich aquifer (Portugal). (September 2018) - Marques, J.M.; Etiope, G.; Neves, M.O.; Carreira, P.M.; Rocha, C.; Vance, S.D.; Christensen, L.; Miller, A.Z.; Suzuki, S.
Abstract: Continental active serpentinization of ultramafic rocks is today recognized as a key process triggering a sequence of phenomena involving the passage from inorganic, to organic and metabolic reactions. These may have a role in the origin of life, and may explain the occurrence of abiotic hydrocarbons on Earth and other planets. Production of hyperalkaline waters and abiotic methane (CH4 ) are two critical steps in this sequence. They were described independently by specific hydrogeological and geochemical models. Here, we update and combine these models into a unified scheme using and integrating geological, hydrogeological, hydrogeochemical, gas-geochemical and microbial analyses acquired from 2002 to 2014 in the Cabeço de Vide (CdV) study site, Portugal. The hyperalkaline (pH > 10.5), Na-Cl/Ca-OH mineral water of CdV evolve from groundwater-peridotite interaction (serpentinization) generating hydrogen (H2 ), which, according to multiple theoretical, laboratory and field evidence, likely reacted with CO2 within metal- (catalyst) rich rocks, abiotically producing CH4 (up to 1.2 mg/L; -24.4°/oo  < δ 13 C-CH4  < -14.0°/oo and -285°/oo  <  δ 2 H-CH4  < -218°/oo ). The hyperalkaline water hosts hydrogen oxidizing bacteria " Serpentinomonas ", which may explain the paucity of H2 observed in the dissolved gas. The CdV gas-rich mineral waters ascend along a fault at the boundary of the peridotite intrusion. Temporal changes of pH and CH4 concentration result from episodic mixing with shallower Mg-HCO3 -type waters. Soil-gas analyses show that methane migrates to the surface along the fault, also independently from the water emergences, consistently with non-aqueous abiotic CH4 production. Our integrated model is generally compatible with observations from other gas-bearing continental serpentinization sites. Highlights: Combined hydrogeological and gas-geochemical models of hyperalkaline waters. Gas flow along a fault is disconnected from serpentinization water springs. No methanogenic activity detected. Microbial H2 consumption detected. Conceptual water-gas model is compatible with other land-based serpentinization sites.